Appraisal and simulation of expected genetic gain for production and reproduction traits in Sahiwal cattle - RATWAN, POONAM; CHAKRAVARTY, ATISH KUMAR; KUMAR, MANOJ (The Indian Journal of Animal Sciences, 2021)
The present study was undertaken with an objective to assess the expected genetic gain for production and reproduction traits, viz. 305-day milk yield (305DMY), average daily milk yield (ADMY), and calving to first insemination interval (CFI) in Sahiwal cattle. Data spread over a period of 29 years pertaining to production and reproduction traits of Sahiwal cattle maintained at an organized herd of ICAR-National Dairy Research Institute, Karnal, were utilized. Expected genetic gain per generation was assessed based on first and pooled 6 lactation records using 2 different methods, i.e. method I (ΔG = h2S) and II (ΔG = iσph2). Method II, which considered selection intensity and phenotypic standard deviation of the traits led to better estimation in Sahiwal cattle. Further, different parameters involved in methods I and II were simulated to evaluate the expected genetic gain in first lactation traits, viz. 305DMY, ADMY, and CFI. In method I, generation interval was decreased as well as increased for estimating expected genetic gain. Using method I, expected genetic gain increased by about 33, 33, and 43% for 305DMY, ADMY, and CFI with the reduction of generation interval (GI) from 5.31 to 4 years, whereas the expected genetic gain decreased by about 11, 17 and 14% for the above-mentioned traits, respectively, with the increase of GI from 5.31 to 6 years. In method II, with the increase of selection intensity and reduction of GI, a significant increase in ΔG/year for 305DMY, ADMY, and CFI was observed. Present study indicated that generation interval and proportion of Sahiwal animals selected should be less than 5 years and 75%, respectively, for achieving more than 50% expected ΔG/year for 305DMY, ADMY, and CFI in an organized herd.